Designing a two - Dimensional animation for verbal apraxia therapy for children with verbal apraxia of speech - Rahim, Sarni Suhaila; Parumo, Shahril; Hidayat, Muhammad Taufik; Muhammad Sani, Muhammad 'Ammar; A’bas, Nurul Najihah; Abdul Aziz, Hilmi (International Information and Engineering Technology Association, 2022)
Verbal Apraxia, also called Apraxia of Speech (AOS) is a speech sound condition that affects a person’s ability to translate conscious speech goals into motor plans, resulting in limited and difficult communication. This article presents an investigation on the designing of a 2D animation and its use as a therapy for Verbal Apraxia. This paper aims to investigate animation principles and to design and develop an animation video as a therapeutic solution. The expected outcome of this paper is a comprehensive analysis of the cognitive training in verbal therapy while focusing on spreading awareness of verbal apraxia towards society. In conclusion, this animation video runs successfully and meets all the objectives completely. Therefore, this proposed 2D animation is expected to contribute as a teaching syllabus for special needs schools and produce great usability for the users.